The atomic structure and dynamics at the CaCO3 vaterite-water interface: A classical molecular dynamics study - Schuitemaker, Alicia; Raiteri, Paolo; Demichelis, Raffaella (2021)
Classical molecular and lattice dynamics were applied to explore the structure and dynamics of water on different surfaces of vaterite, the least abundant calcium carbonate polymorph. Surfaces were generated starting from the three possible structural models for vaterite (monoclinic, hexagonal/trigonal, and triclinic) and pre-screened using their surface energies in an implicit solvent. Surfaces with energies lower than 0.55 J/m2 were then run in explicit water. The majority of these surfaces dissolve in less than 100 ns, highlighting the low stability of this phase in abiotic environments. Three stable surfaces were identified; they exhibited only minor structural changes when in contact with explicit water and did not show any tendency to dissolve during 1 µs molecular dynamics simulations. The computed water density profiles show that all these surfaces have two distinct hydration layers. The water residence time at the various calcium sites was computed to be within 0.7 and 20.5 ns, which suggests that specific Ca ions will be more readily available to bind with organic molecules present in solution. This analysis is a step forward in understanding the structure of this complex mineral and its role in biomineralization, as it provides a solid theoretical background to explore its surface chemistry. In particular, this study provides realistic surface models and predicts the effect of water exchange at the surface active sites on the adsorption of other molecules.